DEMOKRASI DAN PEMBANGUNAN - Siti Witianti (Universitas Padjadjaran, 2016)
The relations between democray and development has become wide discussion since world war two until now. The question rised whether democracy supports development or development supports democracy both in central and local level. Democracy has been choosed in manycountries. Democracy marked by participation needed in development. Furthermore, democracy needs better people’s capacity which only can be done in the development process. Comprehensive development concept stresses on the people. People become subject and object in the development. People’s participation makes the result of development suits with the need of the people. There is an opinion that comprehensive development process might support democratization process.